2022
DOI: 10.57177/idn.v15.11
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction, an invisible complication of diabetes – an exploratory study of the experiences of premenopausal women with Type 1 diabetes

Abstract: Background: Survey data suggest that women with Type 1 diabetes mellitus have a higher prevalence of sexual dysfunction (SD) compared with women with Type 2 diabetes or without diabetes. However, little is known about how women with Type 1 diabetes experience SD or its impact on their lives. This exploratory study sought to elicit women with Type 1 diabetes’s experiences of SD and identify their ideas on how SD could be better addressed in diabetes care. Method: A qualitative study using semi-structured interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…While this review has shown that the prevalence of SD is much higher in women with type 1 diabetes, this estimate is based on generic SD measure. Previous qualitative studies have shown that women with type 1 diabetes experienced SD in multiple ways 13,35,36 that are not captured by these generic measures. Hence, the studies included in the review may have underestimated women with type 1 diabetes experiences of SD.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While this review has shown that the prevalence of SD is much higher in women with type 1 diabetes, this estimate is based on generic SD measure. Previous qualitative studies have shown that women with type 1 diabetes experienced SD in multiple ways 13,35,36 that are not captured by these generic measures. Hence, the studies included in the review may have underestimated women with type 1 diabetes experiences of SD.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of SD in this population raises an important question about the extent to which it is considered in clinical care. SD can have a significant detrimental impact on quality of life and relationships 1,11,13 . However, while SD is commonly considered and addressed in men with diabetes, it is not routinely explored in women 11,31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations